ASSOCIATION AND INTERDEPENDENCY AMONG THE STOCK MARKETS OF SEVERAL FORMER YUGOSLAV COUNTRIES - Arsov, Sasho (RSEP, 2017)
The article explores the long- and short-run association among the capital markets of several countries that emerged from the collapse of former Yugoslavia, as well as their dependency with one of the mature European markets. Two econometric techniques have been used to explore the inter-market linkages and the mutual influence among the markets. The Johansen cointegration framework applied to five markets pointed to the existence of one cointegrating vector, but the results could not be validated through standard tests. The Vector Autoregressive model revealed certain causal dependencies among the markets. These relationships should be understood as chronological ordering of the market trends, rather than as real spillovers of information or capital among the countries. These conclusions should teach the investors that they should closely follow the trends in the leading markets in order to provide themselves with timely information related to the composition of their portfolios.
Keywords: stock markets, volatility, cointegration, interdependency, portfolio